Vascular smooth muscle cells ablation with endovascular non thermal irreversible electroporation - Maor, Elad (2010)
PURPOSE: Using fundamental principles of electroporation and mathematical analyses of temperature and electrical fields of blood vessels we developed an endovascular ablation approach - non thermal irreversible electroporation (NTIRE). The purpose of this study was to evaluate the effect of endovascular NTIRE on blood vessels. MATERIAL AND METHODS: Specially made endovascular devices with four electrodes on top of inflatable balloons were used to apply electroporation pulses. Finite element simulations were used to characterize NTIRE protocols that will not induce thermal damage to treated tissues. Right iliac arteries of eight rabbits were treated with 90 NTIRE pulses. Angiograms were preformed before and after the procedures. Arterial specimens were harvested at 7 and 35 days. Evaluation included Hematoxylin & Eosin, elastic Von Giessen, and Masson’s Trichrome stains. Immunohistochemistry of selected slides included smooth muscle actin, proliferating cell nuclear antigen, von willebrand factor and S-100 antigen. RESULTS: At 7 days, all NTIRE-treated arterial segments displayed complete, transmural ablation of vascular smooth muscle cells (VSMC). At 35 days, similar damage to VSMC was noted. In most cases, elastic lamina remained intact and endothelial layer regenerated. Occasional mural inflammation and cartilaginous metaplasia were noted. After five weeks there was no evidence of significant VSMC proliferation, with the dominant process being wall fibrosis with regenerated endothelium. CONCLUSIONS: NTIRE can be applied in an endovascular approach. It efficiently ablates vessel wall within seconds and with no damage to extra-cellular structures. NTIRE has possible applications in many fields of clinical cardiology, including arterial restenosis and cardiac arrhythmias.